An experimental investigation on energy-effective additive manufacturing of aluminum parts via process parameter selection. (10th January 2021) - Peng, Tao; Lv, Jingxiang; Majeed, Arfan; Liang, Xihui
Abstract: This paper investigates the influences of process parameters on part quality, electrical energy consumption, and corresponding energy effectiveness (EE) of AlSi10Mg specimens fabricated by selective laser melting (SLM). Here, EE is defined as the ratio between equivalent quality and specific energy consumption (SEC), where SEC refers to the energy consumption per kilogram of part produced during the building process. The reduction of electrical energy without significantly compromising quality via process parameter configuration was studied. Three parameters, laser power, scan speed and overlap rate, were selected and full factorial design was employed. Single track and single layer experiments were conducted to determine the ranges of process parameters, and multiple layer specimens were prepared for the testing of quality performances, including density, tensile strength, and hardness. The energy consumption of the auxiliary system and laser of the SLM machine were measured for SEC calculation. Results show that the density does not increase with increased SEC, while the tensile strength and hardness show increasing trends. EE can be improved without significantly sacrificing density and hardness, but the tensile strength will be greatly reduced. A case showed that a significant percentage (27.8%) of electrical energy could be saved while satisfying the quality requirements via proper selection of process parameters for the manufacturing of SLMed parts. The findings will help process designers to foster the sustainability of additive manufacturing. Highlights: Part quality and energy consumption of SLM processes were jointly studied. Energy effectiveness (EE) is proposed to quantify the analysis results. Energy consumption can be reduced without significantly compromising part density. Achieving higher tensile strength and hardness of AlSi10Mg parts consumes more energy. EE can be improved by increasing scan speed and decreasing overlap rate.